К изучению Ostracoda Азовского и Черного морей - (:unkn) unknown (Наукова думка, 1965)
Ostracods which represent subfamilies Loxoconchinae G.O. Sars and Paradoxostominae Brady et Norman and inhabit the Black Sea and the Sea of Azov are discussed. Samples taken near the Crimean and the Caucasian shores of the Black Sea and in the Bosphorus area by researchers of the Sevastopol Biological Station and samples collected by the author from different areas of the Black Sea and the Sea of Azov (700 samples altogether) were examined. As the result, the biology and distribution of species already acknowledged for the two seas were defined more accurately and some new forms found. Several samples from different locations of the Mediterranean Sea were kindly offered by M.I. Kiseleva (Sevastopol Biological Station) that enabled comparison between some ostracods from the Azov-Black sea basin and the forms from the Mediterranean Sea. The recent record includes 25 species out of which some are new, first found in the Azov-Black sea basin and in the Soviet sector of the Black Sea (7, 3 and 8, correspondingly).
On the study of Ostracoda from the Sea of Azov and the Black Sea